2020
DOI: 10.3390/rs12010170
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Citrus Tree Health Using True Color UAV Images

Abstract: Huanglongbing (HLB) and Phytophthora foot and root rot are diseases that affect citrus production and profitability. The symptoms and physiological changes associated with these diseases are diagnosed through expensive and time-consuming field measurements. Unmanned aerial vehicles (UAVs) using red/green/blue (RGB, true color) imaging, may be an economic alternative to diagnose diseases. A methodology using a UAV with a RGB camera was developed to assess citrus health. The UAV was flown in April 2018 on a grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Zhang et al (2020), Hunt Junior et al (2018 and Schirrmann et al (2016) also found weak results monitoring the N variability with RGB imagery in maize, potatoes, and winter wheat, respectively. Garza et al (2020), did not find significant correlation with the visible VI Triangular Greeness Index (TGI) and the amount of N in citrus trees. However, Zhang et al (2020) reported that the Excess Green (ExG) may have the potential for this task, and Schirrmann et al (2016) found positive relationships with other biophysical parameters of the crop, like fresh and dry biomass, and Leaf Area Index.…”
Section: Random Forest Modelsmentioning
confidence: 89%
See 1 more Smart Citation
“…Zhang et al (2020), Hunt Junior et al (2018 and Schirrmann et al (2016) also found weak results monitoring the N variability with RGB imagery in maize, potatoes, and winter wheat, respectively. Garza et al (2020), did not find significant correlation with the visible VI Triangular Greeness Index (TGI) and the amount of N in citrus trees. However, Zhang et al (2020) reported that the Excess Green (ExG) may have the potential for this task, and Schirrmann et al (2016) found positive relationships with other biophysical parameters of the crop, like fresh and dry biomass, and Leaf Area Index.…”
Section: Random Forest Modelsmentioning
confidence: 89%
“…On the same leaves that were analyzed, we used the chlorophyll meter SPAD 502, performing 2 readings per leaf, and registering the average for each point, that is, 16 readings per point. The SPAD values are given by the difference between the transmittance of red and infrared light that penetrated the leaf (Garza et al, 2020), and the objective of obtaining these values was to verify their relationship with the measured amounts of N.…”
Section: Study Area and Leaf Samplingmentioning
confidence: 99%
“…Maximum winds were recorded for each flight with a Skywatch Meteos windmeter anemometer (30 m AGL flight = 5 km/h; 40 m AGL flight = 15 km/h; 50 m AGL flight = 7 km/h). Our lowest flight altitude was 30 m AGL; this altitude was used in a similar study for agricultural crops in the same region [45] and we increased the altitude by 10 m increments up to 50 m AGL. This allowed us to assess the effect of pixel resolution on forage estimation.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…For our study we set our flight settings to a double grid style flight pattern, at a speed of 3-5 km/h, 70 • camera angle, with 80% image overlap using the Pix4D capture application for Android. The use of convergent image networks to develop photogrammetric models using structure for motion can help improve the reconstruction accuracy of these models [25,45,46]. The UAV flight was controlled through auto-pilot mode in this program.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…It has been found that the high-precision recognition of citrus canker can be achieved indoors or in air. Garza et al [20] used RGB UAV remote sensing to detect citrus HLB and foot rot and explained the subtle differences in tree health caused by various diseases through the triangular green index (TGI).…”
Section: Introductionmentioning
confidence: 99%